The Parkinson's disease nurse specialist and subcutaneous apomorphine infusion. A Scoping Review of the literature - Conte, Luana; Lezzi, Pierluigi; Lupo, Roberto; Fasano, Antonio; Carvello, Maicol; Lezzi, Tania; Artioli, Giovanna; Vitale, Elsa; Rubbi, Ivan; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2024)
Objective: The aim of this scoping review is to outline the scientific evidence concerning the role of Parkinson's disease nurse specialists (PDNS) to provide education and guidance to patients with Parkinson's disease (PD) undergoing subcutaneous apomorphine therapy (CSAI).Introduction: PD affects approximately 1% of both men and women on a global scale, especially those aged 60 and above. Working within a multidisciplinary team, the PDNS enhances adherence to the treatment regimen, even in a home-based setting.Inclusion criteria: Included studies involved participants over 18 years old, with texts in English or Italian. Exclusions covered research on alternative apomorphine administrations, brain stimulation, comparisons with other treatments, mood changes from apomorphine, or unrelated to PDNS training.Methods: We conducted a comprehensive literature review across databases such as Medline (via PubMed), The Cochrane Library, Scopus, Web of Science (WOS), and Google Scholar, sourcing relevant articles to identify primary indexed studies examining the interaction between nurse practitioners and PD patients undergoing subcutaneous apomorphine treatment.Results. The review encompasses twenty studies, revealing that specialized nursing education and training during the subcutaneous apomorphine therapy phase can effectively mitigate the considerable risks associated with treatment nonadherence.Conclusions: The collaboration of proficient and specialized nursing personnel, working alongside a multidisciplinary team, to deliver suitable training and education during CSAI, is instrumental in averting adverse outcomes and potential nonadherence issues, thereby enhancing the quality of life for both PD patients and their caregivers.